(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
A full-diallel cross comprising eight varieties belonging to four different maturity groups was developed and studied for some selected characters to determine the nature of gene action of parents and hybrids. Eighty-one genotypes comprising of crosses, reciprocals, selfs, parents and nine checks were evaluated at Kadawa under irrigation using two different planting dates (environments). The results for environments one, two and combined across environments, revealed that the magnitudes of General Combining Ability (GCA) components were much higher than that of Specific Combining Ability (SCA) for days to 50% tasselling, days to 50% silk, number of leaves per plant and number of kernels per row indicating the predominance of additive gene action controlling the traits, where SCA is small relative to GCA, performance of single cross progeny can be predicted on the basis of the GCA of the parents. Those traits having higher SCA components to that of GCA were controlled by the non-additive type of gene action, revealed that these traits were purely under dominance effect of gene and that, selection for these traits should be performed using recurrent selection method. High variance components due to reciprocals for plant height, ear height and grain yield for both environments and combined indicating the importance of maternal effects for these characters.